DEVELOPMENT OF FRUIT LEATHER FROM ACTINIDIA ARGUTA BY-PRODUCT: QUALITY ASSESSMENT AND SHELF LIFE STUDIES - GIACALONE, G.; DA SILVA, T.M.; PEANO, C.; GIUGGIOLI, N.R. (Italian Journal of Food Science, 2019)
Strategies are needed to reduce the substantial fruit losses of Actinidia arguta (speciality fruits) caused by the high perishability of the edible skin. Fruit leathers are considered a valuable opportunity to meet the requirements of today’s consumers searching for healthy and time-saving products. This work aimed to (a) develop a novel baby kiwifruit leather product (four formulations) and (b) evaluate the best formulation under different shelf life conditions. Storage at 25°C and polyethylene samples presented the best colour and received acceptable scores for sensory evaluation at the end of the shelf life.